Increasing the Well-Being of Others On-the-Job and Outside the Workplace - Max van Lent (Tinbergen Institute, 2017)
We study the relationship between workers' opportunities to help others on-the-job and volunteering behavior outside the workplace. We predict that there is substitutability between workers' contribution to other peoples' well-being by exerting effort on-the-job and outside the workplace. We test this prediction using rich data from the Dutch LISS Panel. We exploit variation in workers' opportunities to help others on-the-job from two sources: i) workers' job switching behavior and ii) changes in workers' opportunities to help others on their current job through plausibly exogenous changes in workers' match of mission preferences with their employer. We find some support for our prediction.
Keywords: D64; H11; J45; M50; 330; altruism; charitable donations; volunteering; public sector employment; job switchers; mission motivation